Is There an Epigenetic Component Underlying the Resistance of Triple-Negative Breast Cancers to Parp Inhibitors? - Lovato, Amanda; Panasci, Lawrence; Witcher, Michael (Frontiers in Pharmacology, 2012)
Poly(ADP-ribose)polymerase (Parp) is an enzyme responsible for catalyzing post-translational modifications through the addition of poly(ADP-ribose) chains (known as PARylation). Modification by PARylation modulates numerous cellular processes including transcription, chromatin remodeling, apoptosis and DNA damage repair. In particular, the role of Parp activation in response to DNA damage has been intensely studied. Tumors bearing mutations of the breast cancer susceptibility genes, Brca1/2, are prone to DNA breakages whose restoration into functional double-strand DNA is Parp dependent. This concept has been exploited therapeutically in Brca mutated breast and ovarian tumors, where acute sensitivity to Parp inhibitors is observed. Based on in vitro and clinical studies it remains unclear to what extent Parp inhibitors can be utilized beyond treating Brca mutated tumors. This review will focus on the often overlooked roles of PARylation in chromatin remodeling, epigenetics and transcription to explain why some cancers may be unresponsive to Parp inhibition. We predict that understanding the impact of PARylation on gene expression will lead to alternative approaches to manipulate the Parp pathway for therapeutic benefit.